Translation Criticism and the Problem of the Term: Dictionaries of Kurdish Literary Criticism as Examples - Karzan Kareem Ameen (Zanco Journal of Human Sciences, 2025)
This is a qualitative study, conducted through critical analysis and comparison of concepts, forms, and definitions of terms from their original sources to how they were constructed, translated, and entered into Kurdish literary criticism dictionaries, with the goal of determining the types and sources of problems. The dictionaries and glossaries are: "Dictionary of Literary Terms" and "Analytical Dictionary of Literary Terms" prepared by Bakhtiar Sajjadi and Muhammad Mahmoudi; "Literary Terms" prepared by the Literature Committee of the Kurdistan Scientific Academy; "Dictionary of Literary and Critical Terms" by Nawzad Ahmad Aswad; "Literary Dictionary" by Mohsen Ahmad Omar; "A Dictionary of Critical Terms" by Bakhtiar Sajjadi; "Keywords: Dictionary of Literature and Criticism ” by Abdullah Taher Barzanji and Ali Taher Barzanji.It is a cognitive attempt to clarify and determine the types of problems, their causes, how to resolve contradictions and ambiguities in the translation and formulation process, and the issue of objectivity in formulating the meaning and concept of some of the terms found in dictionaries. The most essential issues regarding the form and meaning of terms are divided into three categories: formation, concept, and definition.